2015
DOI: 10.1016/j.jbusres.2014.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Linking female entrepreneurs' motivation to business survival

Abstract: Analysis of entrepreneurs' motives in the framework of organizational behavior theory is a popular research area regarding female entrepreneurship. This study analyzes women entrepreneurs' motives (propensity for risk, finding a work-life balance, desire to develop business skills, need to seek self-employment, and desire to earn more than in paid employment) to achieve survival of their businesses through crisp set qualitative comparative analysis (csQCA). Analysis yields the following results: 1) women whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 45 publications
3
84
1
10
Order By: Relevance
“…Although based on a small sample of self-employed, Rey-Martí et al (2015) find that women who state that they became self-employed to pursue a better work-life balance are less likely to succeed. Hughes (2006) also finds indications that women who state that they became self-employed for Bwork-family^reasons have lower incomes from self-employment than those having Bclassic^motives such as independence, challenge, and financial independence.…”
Section: Self-employment Entry After Childbirthmentioning
confidence: 92%
“…Although based on a small sample of self-employed, Rey-Martí et al (2015) find that women who state that they became self-employed to pursue a better work-life balance are less likely to succeed. Hughes (2006) also finds indications that women who state that they became self-employed for Bwork-family^reasons have lower incomes from self-employment than those having Bclassic^motives such as independence, challenge, and financial independence.…”
Section: Self-employment Entry After Childbirthmentioning
confidence: 92%
“…Since its initial development in the mid-1980s at [74], and extended to the current year by the work of Ragin [75], Cronqvist and Berg-Schlosser [76], QCA methodology has spread successfully across the disciplines of business administration and management (see [12,[77][78][79][80]). …”
Section: Empirical Methodologymentioning
confidence: 99%
“…As we can see, both reasons relate to discrimination against women in the labour market. Nevertheless, other studies (Herron and Robinson 1993;Rey-Martí et al 2015) have demonstrated that business expansion also depends on business owners' motivation and on attitude and intention with respect to the future of the business. Along these lines, other studies (Fischer et al 1993;Rosa et al 1996;Du Rietz and Henrekson 2000) have reported that business size is also related to women business owners' motivations and attitudes towards expansion, which differ from those of male business owners.…”
Section: Factors Related To Barriers To Women Entrepreneurshipmentioning
confidence: 96%